Behavior of Ad Hoc routing protocols, analyzed for emergency and rescue scenarios, on a real urban area - Enciso Quispe, L. (2017)
A mobile Ad Hoc network (MANET) is a collection of wireless mobile nodes that can dynamically configure a network without a fixed infrastructure or central administration. This makes it ideal for emergency and rescue scenarios, where sharing information is essential and should occur as soon as possible. This article discusses which of the routing strategies for mobile MANETs: proactive, reactive or hierarchical, has a better performance in such scenarios. By selecting a real urban area for the emergency and rescue scenario, we calculated the density of nodes and the mobility model needed for the validation study of AODV, DSDV and CBRP in the routing model. The NS2 simulator has been used for our study. We also show that the hierarchical routing strategies are better suited for this type of scenarios.